2017
DOI: 10.3390/catal7060184
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Acetalization: An Efficient Strategy for High-Value Utilization of Biodiesel-Derived Glycerol

Abstract: Abstract:In this study, an efficient process for high value utilization of biodiesel-derived glycerol was proposed via a simple reaction of acetalization catalyzed by novel catalysts of ester sulfate-functionalized ionic liquids (ILs). The relationship between the IL structure and its catalytic activity was investigated. The effects of reaction conditions, and the substrate adaptability, were also carefully studied. The results demonstrate that ester sulfate-functionalized IL shows excellent catalytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The drawback of this system was its very long reaction time (21–36 h). Generally, the reaction of glycerol with aldehydes/ketones is conducted under homogenous Lewis catalysts (Ruiz et al, 2010 ) or mineral acids such as HF, HCl, H 3 PO 4 , H 2 SO 4 , and p-toluenesulfonic acid (pTSA) to form solketal (1,2-isopropylidene glycerol, 2,2-dimethyl-1, or 3-dioxolane-4-methanol) (Sato et al, 2008 ; Coleman and Blankenship, 2010 ; Suriyapradilok and Kitiyanan, 2011 ; Nanda et al, 2014a ; Sun et al, 2017 ). The first generation of studies was stopped more than half a century ago due to the economic barriers.…”
Section: Catalytic Acetalization Of Glycerolmentioning
confidence: 99%
“…The drawback of this system was its very long reaction time (21–36 h). Generally, the reaction of glycerol with aldehydes/ketones is conducted under homogenous Lewis catalysts (Ruiz et al, 2010 ) or mineral acids such as HF, HCl, H 3 PO 4 , H 2 SO 4 , and p-toluenesulfonic acid (pTSA) to form solketal (1,2-isopropylidene glycerol, 2,2-dimethyl-1, or 3-dioxolane-4-methanol) (Sato et al, 2008 ; Coleman and Blankenship, 2010 ; Suriyapradilok and Kitiyanan, 2011 ; Nanda et al, 2014a ; Sun et al, 2017 ). The first generation of studies was stopped more than half a century ago due to the economic barriers.…”
Section: Catalytic Acetalization Of Glycerolmentioning
confidence: 99%
“…In [17], the authors used sulfonic ILs in the acetalization reaction of cyclohexanone and glycerin. They showed that the sample [MeSO 3 bmim][MeSO 4 ] is capable of achieving glycerol conversion of up to 86% (Table 3), with a selectivity for six-membered acetal of 28%.…”
Section: Homogeneous Catalysts For Acetalizationmentioning
confidence: 99%
“…To produce value-added chemical compounds, oxidation, dehydration, acetylation, and ammoxidation can be used. Of special interest are the acetalization reactions of glycerol from biodiesel processes into various oxygenated fuel additives [16][17][18]. A literature review was conducted to identify the number of articles published in the journals indexed in Web of Science and Scopus using a basic search for the articles containing information about the formation of acetals or ketals from glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional chemical syntheses are the most widely used methods in the large-scale preparation of glycerol carbonate directly from glycerol. With glycerol used as starting material, glycerol carbonate is obtained via chemical processes, such as carbonation with carbon dioxide [26][27][28] or carbon monoxide in the presence of oxidants [29,30], trans-carbonation with phosgene [21] or urea and its derivatives [31][32][33][34][35], and transesterification with simple carbonate esters (Figure 3) [15][16][17][18][19][20]. Transesterification of glycerol has significant advantages over other methodologies in the following aspects: (1) avoiding the employment and release of poisonous gases and toxic reagents; (2) higher activity and selectivity; (3) shorter reaction time and higher conversion; (4) free of solvent and simple separation of catalyst; and (5) environmentally friendly and intrinsically safe.…”
Section: Introductionmentioning
confidence: 99%